Electrochemical investigation of double layer surface-functionalized Li-NMC cathode with nano-composite gel polymer electrolyte for Li-battery applications. (10th December 2022) - Singh, Shishir K.; Dutta, Dimple P.; Gupta, Himani; Srivastava, Nitin; Mishra, Raghvendra; Meghnani, Dipika; Tiwari, Rupesh K.; Patel, Anupam; Tiwari, Anurag; Singh, Rajendra K.
Highlights: The RGO-wrapped Li2MoO4@Li-NMC111 cathode material and nano-composite gel polymer electrolytes (NGPEs) are developed for rechargeable Li-battery. 5 wt.% MCM-41 containing NGPE shows high lithium transference number and Li-ion conductivity at 30 °C ( t L i + = ∼ 0.49 and σ L i + = ∼4.4 × 10−3 s cm−1). The RGO-wrapped Li2MoO4@Li-NMC111 cathode shows better Li-ion diffusion coefficient, rate capability and specific energy density as compare to pristine cathode. The Li/5 wt.% MCM-41 containing NGPE/RGO-wrapped Li2MoO4@Li-NMC111 cell delivers the specific energy density of ∼728 mWh g  − 1 at 0.2C at 30 °C. 5 wt.% MCM-41 containing NGPE shows better cycle stability at 30 °C and 70 °C as compare to the commercial LiPF6:EC:DEC:DMC electrolyte. Abstract: A long cycle-stability and safety is key requirement for the large-scale application of rechargeable Li-batteries. In this study, a thin double-layer (reduce graphene oxide and Li2 MoO4 ) coated Li-NMC111 cathode is successfully synthesized which delivers improved electrochemical performance such as higher specific energy density and better rate capability, as compared to the pristine Li-NMC111. Furthermore, a freestanding/flexible nano-composite gel polymer electrolyte (NGPEs) is successfully prepared by solution cast technique and found suitable for high-temperature Li-battery applications. The developed 5 wt.% MCM-41 containing NGPE (NGPE#1) not only facilitates enhanced Li-ion conductivity of ∼4.4 ✗ 10 −3 S cm −1 at 30 °C but also prevents uncontrolled lithium dendrite growth. The RGO-wrapped Li2 MoO4 @Li-NMC111 cathode with optimized NGPE#1 delivers high specific discharge capacity (∼211 mAh g − 1 at 0.2C and ∼157 mAh g − 1 at 0.5C) and specific energy density (∼728 mWh g − 1 at 0.2C and ∼520 mWh g − 1 at 0.5C) as compared to pristine Li-NMC111 cathode. Moreover, after 100 cycles, the discharge capacity of RGO-wrapped Li2 MoO4 @Li-NMC111 with optimized NGPE#1 is obtained ∼150 mAh g − 1 at 0.5C, with 75% capacity retention of the maximum capacity. In addition, at 70 °C, the specific discharge capacity of Li/RGO-wrapped Li2 MoO4 @Li-NMC111 cell with optimized NGPE#1 is obtained ∼186 mAh g − 1 at 0.5C. Graphical abstract: Image, graphical abstract